Development of Cell phone Straps Beading Vocational Training Program for Children with Intellectual Disabilities - Fitri Maulidazani; Cece Rakhmat; Iding Tarsidi; Wulan Syakinah Munggaran Sari; Oom Sitti Homdijah; Riksma Nurahmi Rinalti Akhlan (Jurnal Pendidikan (Teori dan Praktik), 2026)
Training provided to children with special needs is increasingly developing along with the advancement of human resource thinking. These training are assisted by the presence of technology that provides easiness for individuals to obtain information easily and quickly, as well as to foster innovation, including in the creation of handicrafts. An example of the handicraft innovation is stringing cell phone straps. This research used a field study method to collect data directly and evaluate real situations. The research objectives are developing educational programs for children with intellectual disabilities, validating theories with field evidence, and gaining practical insights into the studied problems. The implementation was carried out to three students. All students were able to follow well and showed significant progress when working on the stages of making cell phone straps from the beginning to the packaging stage. Vocational programs that focus on making cell phone straps for children with intellectual disabilities provide valuable opportunities for them to develop practical skills and creativity. Through this activity, children can learn to use various simple materials and tools to create other products that have economic advantages.